Role of serum fibroblast growth factor-23 and Klotho level in COVID-19 infection-related mortality: a prospective study - Davut Akin; Burcu B Aydogan; Nilufer Emre; Gulsah Gundogdu; Sehmus Ozmen; Ozgen K Erkek; Mehmet Alpua (Journal of Infection in Developing Countries)
Introduction: This study investigated the role of fibroblast growth factor 23 (FGF23)/Klotho in the mortality of patients hospitalized with coronavirus disease 2019 (COVID-19), excluding those with chronic kidney disease (CKD).